Production and diagnostics of spin-polarized heavy ions in the sequential two-electron radiative recombination - Maiorova, Anaa V.; Surzhykov, Andrey; Tashenov, Stanislav; Shabaev, V. M.; Stöhlker, Th (Physica scripta, 2013)
The sequential radiative recombination of initially bare ions, which are collided with two spatially separated electron targets, is studied. It is demonstrated that the magnetic sublevel population of H-like ions, which are formed due to electron capture from the first target, depends on the first radiative recombination (RR) photon emission direction. Such a relative population, which can be parameterized in terms of the polarization parameters, affects then the angular and polarization properties of the second photon emitted in the collision with the second target. The coincidence γ-γ RR measurements may allow us to study, therefore, the process in which (i) H-like ions of some particular polarization are ‘selected out’ of the beam by detecting first recombination photons and (ii) this polarization is ‘measured’ in the second electron capture process. In order to describe the output of the (future) γ-γ correlation measurements, we derive the general expression for angular- and polarization-correlation function. Detailed calculations for the dependence of this function on the experimental setup and collision energy are performed for the RR of bare uranium ions.
Gesehen am 16.06.2021